THE EFFECT OF DIFFERENT SALT CONCENTRATION ON CHOLESTEROL OF WHITE SHRIMP (Penaeus indicus) DURING BOILING PROCESSED - Rommy Novrihansa; Rahman Karnila; Suparmi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis study was intended to evaluate the effect of salt concentration on cholesterol of whiteshrimp during boiling processed. There were 2 step in this study: 1) Analyze the cholesterol andnutrition (protein, fat, moisture) of the fresh white shrimp meat. 2) Analyze the cholesterol andnutrition (protein, fat, moisture) of boiled white shrimp. The white shrimp was boiled with differentsalt concentration for R0,R1,R2 and R3 was 0%,1%,2% and 3% respectively. The result showedthat cholesterol and nutrition (protein, fat, moisture) of fresh shrimp was 134,05 mg/100g, 17,72%,2,42%, 76,14% respectively. The percentage of fresh white shrimp meat was 58,19% on wholeshrimp, and 41,41% on waste of shrimp. The cholesterol measured for R0,R1,R2 and R3 was115,22 mg/100g, 93,78mg/100g, 71,31mg/100g, and 44,48mg/100g respectively. Meanwhile, thenutrition measured to boiling processed with different salt concentration for protein content was17,53%, 15,65%, 12,99%, 10,77% respectively. Fat content was 2,80%, 1,74%, 1,71%, 0,54%respectively. Moisture content was 75,69%, 74,22%, 72,04%, 70,39% respectively.Keyword: Salt, Cholesterol, White Shrimp (Penaeus indicu).